Effects of adolescent asthma education intervention on asthma control in Northwest of Libya - Elfeturi, Nadya Mohamed (2020)
Among adolescents, asthma is an important public health issue that is associated with high morbidity and mortality. Despite most national guidelines consider education as an essential component of effective asthma self-management to promote asthma control and reducing negative impact of this disease on daily life, a little number of educational programs target asthmatic adolescents in Libya. Therefore, the aim of this study was to develop, implement and evaluate the effectiveness of asthma education intervention program on asthma control, asthma knowledge, self-efficacy, asthma quality of life, and pulmonary function test among adolescents with persistent asthma in Northwest of Libya. A parallel randomized controlled trial was conducted in Sabratha Teaching Hospital. A sample of 92 adolescents were randomized by concealment block randomization into either the intervention group (n=46) or the control group (n=46). The asthma educational program for intervention group was held in one day workshop in form of handouts, play role activities, practice session for inhaler devices and booklet. The control group received the same educational program at the end of the study. Delivery of program was based on Social Cognitive Theory. Pre-validated Arabic questionnaires were used to collect the data on demographic characteristics, asthma control, asthma knowledge, self-efficacy, and asthma quality of life. The data were collected at baseline, 3-months, and 6-months post-intervention. Forced expiratory volume in one second (FEV1) was measured by Spiro Pro spirometry at base line and 6-months post intervention. The data was analyzed using SPSS version 22. Generalized Estimating Equation (GEE) was applied to assess the effectiveness of the educational intervention. The results of the current study showed that only 24% of the participants had wellcontrolled asthma. Adolescents whose asthma were well-controlled reported higher level asthma knowledge (OR= 1.224, 95%CI: 1.070- 1.399, p= 0.003), and higher self-efficacy (OR= 1.124, 95%CI: 1.047 – 1.208, p= 0.001), had greater odds of using preventive inhalers every day (OR= 3.355, 95%CI 1.174-9.588, p=0.024), and had three times the odds of not having allergic rhinitis (OR= 3.221 95%CI 1.196- 8.676, p=0.021). There were no significant differences between the two groups regarding the respondents' characteristics and the outcome variables at baseline. The GEE results from the comparisons between groups at 3-months, and 6-months post intervention demonstrated a significant change in asthma control level between the groups across the time (p= 0.008). The adjusted odds of well-controlled asthma among the intervention group was 3.68 (95%CI: 1.42-9.58). For secondary outcomes, compared to the control group, the GEE results showed that participants in intervention group had better asthma knowledge at 3-months (mean difference= 2.53, p= 0.002) and 6- months post intervention (mean difference= 2.94, p< 0.001), higher self-efficacy at 3-months (mean difference= 5.77, p= 0.006) and 6-months post intervention (mean difference= 7.58, p< 0.001), and clinically significant improvement in mean symptoms and limited activity domains of asthma quality of life at 3 months (mean differences = 0.52, and 0.54) and 6-months post intervention (mean differences = 0.74, and 0.61) respectively. However, there was no significant difference between the two study groups in total asthma quality of life, emotional domain of asthma quality of life, and FEV1%. These results provide evidence for the effectiveness of asthma educational program to improve the level of asthma control, as well as the asthma knowledge and self-efficacy among Libyan asthmatic adolescents.